2014
DOI: 10.3389/fpsyg.2014.00423
|View full text |Cite
|
Sign up to set email alerts
|

Adult age-differences in subjective impression of emotional faces are reflected in emotion-related attention and memory tasks

Abstract: Although younger and older adults appear to attend to and remember emotional faces differently, less is known about age-related differences in the subjective emotional impression (arousal, potency, and valence) of emotional faces and how these differences, in turn, are reflected in age differences in various emotional tasks. In the current study, we used the same facial emotional stimuli (angry and happy faces) in four tasks: emotional rating, attention, categorical perception, and visual short-term memory (VS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
2
20
0
1
Order By: Relevance
“…In some studies, older adults performed well at identifying positive expressions (e.g., happiness) but were less able to infer the meaning of posed facial expressions conveying negative affect (e.g., sadness; Calder et al, 2003;McDowell, Harrison, & Demaree, 1994;Moreno, Borod, Welkowitz, & Alpert, 1993; but see differing meta-analytic evidence in Ruffman, Henry, Livingstone, & Phillips, 2008 and see Mather & Knight, 2006 for work on threat perception preservation across adulthood). Other studies find that older adults perceive posed angry and happy faces to be less highly arousing than do younger adults (Svärd, Fischer, & Lundqvist, 2014).…”
mentioning
confidence: 91%
“…In some studies, older adults performed well at identifying positive expressions (e.g., happiness) but were less able to infer the meaning of posed facial expressions conveying negative affect (e.g., sadness; Calder et al, 2003;McDowell, Harrison, & Demaree, 1994;Moreno, Borod, Welkowitz, & Alpert, 1993; but see differing meta-analytic evidence in Ruffman, Henry, Livingstone, & Phillips, 2008 and see Mather & Knight, 2006 for work on threat perception preservation across adulthood). Other studies find that older adults perceive posed angry and happy faces to be less highly arousing than do younger adults (Svärd, Fischer, & Lundqvist, 2014).…”
mentioning
confidence: 91%
“…In contrast, Deckert (2014) showed no age differences regarding natural angry faces as well as neutral, happy, sad, and fearful faces while using a different rating scale than Svard et al (2014). It has to be noted that in the study of Svard et al (2014), the rating took place after processing emotional faces in three different preceding tasks, whereas in Deckert (2014) participants either rated faces in the first place or after rating emotional words. Regarding emotional words, some studies indicate an age-related relation between valence and arousal (e.g., Bjalkebring & Johansson, 2015;Yang & Hasher, 2011).…”
Section: Agementioning
confidence: 94%
“…These aspects presumably add to age differences in the perception of everyday emotional stimuli. Regarding the perception of facial expressions, for example, Svard, Fischer, and Lundqvist ( 2014 ) showed that older adults compared to younger adults perceive less arousal regarding a single averaged, morphed, angry male face as well as a female face, respectively. In contrast, Deckert ( 2014 ) showed no age differences regarding natural angry faces as well as neutral, happy, sad, and fearful faces while using a different rating scale than Svard et al ( 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…sleepiness-activation) (Dalenberg et al, 2014;, whereas for seniors few food-related results have been reported. Although seniors tend to rely more on their emotions and heuristics during various psychological processes, Svärd, Fischer, and Lundqvist (2014) have shown that older persons tend to report emotions with a lower level of valence and emotional arousal than their younger counterparts. However, Svärd et al (2014) did not study food-evoked emotion responses.…”
Section: Introductionmentioning
confidence: 99%
“…reported the occurrence of lower fluctuation of product liking scores among older hyposmic adults. Additionally, Svärd et al, 2014 reported that when persons grow older, they tend to report less extreme ratings for arousal, potency, and valence. Consequently, they may also either experience, or at least report, less extreme ratings for other attributes, like emotions.…”
mentioning
confidence: 99%